Fostering collective intelligence in CPSS: an LLM-driven multi-agent cooperative tuning framework - Chen, Rongjun; He, Chengbo (Frontiers in Physics, 2025)
Cyber-Physical-Social Systems (CPSS) have emerged as a transformative paradigm in recent years, embracing computational processes, physical systems, and human social interactions within an integrated architectural framework. Advances in artificial intelligence technologies are targeted at addressing the complexity of CPSS design, especially in modeling human reactions in cyber-physical environment. Notably, LLM-based agents have shown significant potential, and numerous studies have leveraged multi-agent collaboration frameworks to solve reasoning tasks. Some approaches achieve multi-agent collaboration through a debate or communication setting. However, these approaches only use the existing capabilities of LLMs, fail to enhance their problem-solving performance. Other works incorporate the responses of other LLMs into their training trajectories to train individual LLMs in a reinforcement learning setting. We argue that effective collaboration should align not only in input information but also in consistent optimization objectives. Furthermore, in current cooperative frameworks, some LLMs tend to redundantly repeat others’ viewpoints, contributing minimally to solve problems. In this paper, inspired by multi-agent reinforcement learning research, we propose MACT, a Multi-Agent Cooperative Tuning framework to joint train multiple LLMs, ensuring that the optimization of each agent aligns directly with the objective of the global task. We equip each agent with a critic network to facilitate individual optimization. Furthermore, to encourage different agents to complement each other and contribute to the overall task, we employ a mixing network that ensures the value of each agent is monotonically consistent with the total value. Experimental results reveal that our method significantly enhances cooperative problem-solving capabilities in the LLM multi-agent framework, which set strong evidence for the modeling of human reaction within CPSS.